The small modular molten salt reactor potential and opportunity in Saudi Arabia - Dana Hejazi; Anas M. Alwafi; Salman M. Alzahrani; Meshari M. Alqahtani; Salman M. Alshehri (Nuclear Engineering and Technology)
Molten Salt Reactors (MSRs) represent a promising, safe, advanced nuclear technology that aligns with Saudi Arabia’s Vision 2030 objectives for energy diversification, sustainability, and economic development. This article explores the feasibility and potential impact of implementing MSRs in the Kingdom by assessing some of their technical, environmental, and socio-economic aspects. The research findings indicate that while MSRs may require higher initial capital investments, they offer substantial long-term socio-economic and environmental advantages over conventional power generation technologies. Economic advantages stem from improved fuel efficiency, lower waste management costs, fuel flexibility, load following, job creation, and operational cost savings. Environmental advantages include clean energy production, the ability to utilize thorium as a more environmentally friendly fuel source, the potential of nuclear transmutation for minimizing long-lived radioactive waste, and overall reduced waste output compared to traditional nuclear reactors. While implementing MSRs requires overcoming technical hurdles, mainly related to structural materials withstanding extreme conditions, Saudi Arabia’s thriving research ecosystem is well-suited for overcoming such challenges. The adoption of MSRs presents an opportunity for groundbreaking research, economic diversification, and progression towards a sustainable energy future. With rising energy demands and the need to transition towards cleaner sources, nuclear energy is poised to play a vital role globally and in Saudi Arabia’s future energy mix. This article hopes to raise awareness about the potential of advanced nuclear technologies like MSRs and inspire further research, investment, and conversation within the Kingdom to capitalize on this promising opportunity.